Penguatan Pendidikan Sumber Daya Mineral di SMP Negeri 6 Banda Aceh - Aflah, Nurul; Mirna Rahmah Lubis; Muchlis; Hendra Hasrisman; Pocut Nurul Alam; Husni Husin (Jurnal Mitra Pengabdian Farmasi, 2023)
In this technological era, minerals, in an educational context, refer to components that contribute to overall educational success. Mineral resources serve as the basis for various industries, such as construction, manufacturing, technology, and energy production. This community service activity aims to strengthen the science of high school students at SMP Negeri 6 Banda Aceh so that it can explain the contribution of mineral resources to a country’s Gross Domestic Product. The service team plays a role in providing knowledge of mineral resources to students so that in the future they can develop a basic understanding of earth science. This science strengthening allows students to learn about the formation, properties, and classification of minerals, which are basic concepts in geosciences. The method used is lecture method, question and answer, discussion, and demonstration. The students showed an enthusiastic response to the material presented and participated in the discussion with pleasure.